Text, Palace, Tourism: Exploring Literary Tourism in a Classical Javanese Literature, Wedhatama by King Mangkunegara IV, Central Java, Indonesia - Esti Ismawati; Warsito Warsito; Kun Andyan Anindita (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
Wedhatama, which was published in 1680 at the Surakarta Palace, is still popular today because it contains the concept of tri ugering ngaurip (three philosophies of life), namely arta, (about financial independence), wirya (about honor), and tri winasis (about how to gain intelligence). This study aims to critically examine how Wedhatama, a classic Javanese literary book by King Mangkunegara IV of the Surakarta Palace, contains philosophical values of life and how Javanese culture in the palace can become an interesting literary tourism object. The problem that will be answered in this paper is,